Evaluation of quality level in managing the development of industrial enterprises - Raiko, Diana; Podrez, Olha; Cherepanova, Viktoriia; Fedorenko, Irina; Shypulina, Yuliia (Eastern-European Journal of Enterprise Technologies, 2019)
The research focuses on the substantiation of theoretical aspects and practical support for assessing the quality level of managing enterprises development taking into account the influence of the external and internal environment. The conceptual apparatus for estimation of quality development of enterprise management was refined, which makes it possible to determine reasonably the level of management according to the generally known elements (economic, social and ecological) that are proposed to be supplemented with an energy component. A new conceptual approach to the procedure of evaluation of the quality of development management by levels, the stages of which are proposed to expand by: the formation of the database by levels of management (state, regional), choice and evaluation of indicators by components of development and spheres of activity, development of the tools for management improvement. The integrated indicator has been proposed, which differs from the existing ones by the fact that it estimates the quality of development management, rather than the development level. In contrast to the previously proposed ones, the integrated indicator takes into account the influence of external environment by the components of development and of the internal environment – by the areas of activity for each component. That is why it has practical significance, since it allows performing monitoring and detecting the negative influence of management on the enterprise development. Taking coke plants as an example, the structures of the indicators that characterize the management quality were determined. A large number of indicators were reduced by the method of expert assessments, which increases the validity of the choice. Indicator estimates were constructed solely based on relative indicators (indices), which improves consistency. Using the integrated method, the estimation of the indicators by individual components and on the whole was performed. The scale for evaluation of the quality level of enterprise development management was constructed using the Harrington function. The new approach to assessing the quality of the enterprise development management and a complex of mathematical support will lead to the uniform economic, social, environmental and energy development of enterprises